Corrigendum to “Elemental Sulfur-Based Autotrophic Denitrification in Stoichiometric S0/N Ratio: Calibration and Validation of a Kinetic Model” (Bioresource Technology 2020 307 s0960852420305009 (10.1016/J.Biortech.2020.123229)) - Levican-Jaque, G; Huilinir-Curio, C; Montalvo-Martinez, S; Yanez-Sevilla, D; Acosta-Cordero, L (Elsevier Ltd, 2022)
The authors made typographical errors on the manuscript. The mistakes are: Page 8: The units of the parameter a* must be dm2/mg, not dm2/g. Table five: The parameter k1 and μmax,2 (values calibrated) are wrong. Currently the table shows: Table 5. Calibrated model parameters values obtained, with their confidence interval (CI). [Table presented] It must be: Table 5. Calibrated model parameters values obtained, with their confidence interval (CI). [Table presented] The authors would like to apologise for any inconvenience caused. © 2020 Elsevier Ltd